TECHNOLOGICAL REALITY OF MASS COMMUNICATION AS A RESOURCE POSSIBILITY OF POSTMODERN EDUCATION - Герасимова, Е. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
In the present publication is carried out substantial socio-philosophical analysis of the foundations of the formation of post-modern concept of education in general cultural context, taking into account the impact of the phenomenon of mass communications of modern civilization. We investigate the structural and functional mechanism for updating the national education and the ability to create a lot of variant cultural and educational models.